A "Circuits of Power"-based Perspective on Algorithmic Management and Labour in the Gig Economy; Algorithmisches Management und Arbeitsbeziehungen in der Plattformok̈onomie - Eine "Circuits of Power"-Perspektive - Daniel Pastuh; Mike Geppert (Industrielle Beziehungen, 2020)
The bulk of contributions on digital business so far provide mainly descriptive analyses when it comes to the study of power-related phenomena within the gig economy. We particularly lack systematic, integrative studies which focus on interdependencies of power relations, labour conditions and business model efficiency, based on robust theoretical approaches which capture meso-level structures and micro-level dynamics of power simultaneously. Our conceptual paper addresses this gap by investigating power relations in platform arrangements, based on the framework of "circuits of power". We use the case of the ridesharing platform Uber, which has caused debates in and beyond academia to illustrate how this framework, combined with concepts from labour process theory, behavioural economics and micro-politics, can be applied for a systematic analysis of the diversified portfolio of power-related control and influence mechanisms that are embedded in platforms' software infrastructures. Departing from this, we examine how our approach can inform future research focused on assessing specific forms of management, organisation and work in the wider gig economy. Our discussion concentrates on a) the classification and comparison of heterogeneous forms of gig work; b) the assessment of labour-related problems; and c) power-related organisational dynamics or inertia in such settings. The latter point is related to the central question of why employee voice and resistance are rare in certain gig-work arrangements. – – Vorliegende, vorwiegend deskriptive Beitrag̈e zu digitalen Geschaf̈tsmodellen zeigen die Rolle von Machtverhal̈tnissen zwischen Plattformbetreibern und Plattformarbeitern auf. Machtbeziehungen werden hier sowohl mit organisationalen Gewinnerzielungsabsichten als auch mit problematischen Beschaf̈tigungsbedingungen assoziiert. Obwohl die Forschungslandschaft Beschreibungen und Analysen machtbezogener Phan̈omene im Kontext plattformbasierter Erwerbsarbeit liefert, fehlen bisher holistische Theorieperspektiven, die auf machttheoretischer Grundlage systematisch machtbezogene Phan̈omene auf der Makroebene organisationaler Strukturen und der Mikroebene organisationsinterner Prozesse simultan analysieren. Das konzeptionelle Papier adressiert diese Luc̈ke. Am Beispiel des kontroversen Falls des Fahrdienstleisters Uber illustrieren wir das Potenzial des Konzepts der "Circuits of Power". Wir zeigen, wie die Anwendung des Konzepts in Kombination mit Erkenntnissen der Labour Process Theory, der Verhaltensok̈onomie sowie mikropolitischer Arbeiten erlaubt, das "diversifizierte Portfolio" softwarebasierter Einfluss- und Kontrollpraktiken in Plattformarrangements mit Blick auf ihre Macht-, Effizienz- und Beschaf̈tigungsimplikationen hin integrativ zu analysieren. Hiervon ausgehend zeigen wir das Potenzial dieses Ansatzes, der Analyse von Macht im Feld plattformbasierter Organisation und Arbeit ein theoretisches Fundament zu liefern. Der Ausblick zeigt, wie die Befunde Ansatzpunkte liefern, um a) heterogene Formen plattformbasierter Erwerbsarbeit zu vergleichen, b) die Diskussion ub̈er Probleme plattformbasierter Erwerbsarbeit voranzubringen, und c) systematisch-vergleichend zu beleuchten, warum "endogener" Wandel von Machtverhal̈tnissen durch direkte Interessenartikulation und/oder Widerstand von Plattformarbeitern in spezifischen Plattformarrangements unwahrscheinlich ist.
Keywords: J29; J40; J70; J81; 330; Uber; gig work; platform economy; power; circuits of power; algorithmic management; organisational control; labour conditions; Uber; Gig Work; Plattformok̈onomie; Macht; Circuits of Power; algorithmisches Management; Kontrolle; Arbeitsbedingungen